2021
DOI: 10.1101/2021.09.01.458571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Right fronto-parietal networks mediate the neurocognitive benefits of enriched environments.

Abstract: Exposure to enriched environments (EE) throughout a lifetime, providing so called reserve, protects against cognitive decline in later years. It has been hypothesised that high levels of alertness necessitated by EE might strengthen the right fronto-parietal networks (FPN) to facilitate this neurocognitive resilience. We have previously shown that EE offset age-related deficits in selective attention by preserving grey matter within right fronto-parietal regions. Here, using neurite orientation dispersion and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Specifically, a number of studies have shown that connectivity within the fronto-parietal networks (FPN) accounts for substantial inter-individual variability in neurocognitive resilience in older adults (e.g. (Brosnan et al, 2021;Franzmeier et al, 2017aFranzmeier et al, , 2017bVeldsman et al, 2020)). Recently, we have shown in healthy younger adults that individual differences in connectivity within the dorsal FPN (white matter macrostructural organisation of the superior longitudinal fasciculus (SLF), and resting state functional connectivity within the dorsal FPN) varied according to the CPP build-up rate (Brosnan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a number of studies have shown that connectivity within the fronto-parietal networks (FPN) accounts for substantial inter-individual variability in neurocognitive resilience in older adults (e.g. (Brosnan et al, 2021;Franzmeier et al, 2017aFranzmeier et al, , 2017bVeldsman et al, 2020)). Recently, we have shown in healthy younger adults that individual differences in connectivity within the dorsal FPN (white matter macrostructural organisation of the superior longitudinal fasciculus (SLF), and resting state functional connectivity within the dorsal FPN) varied according to the CPP build-up rate (Brosnan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown in healthy younger adults that individual differences in connectivity within the dorsal FPN (white matter macrostructural organisation of the superior longitudinal fasciculus (SLF), and resting state functional connectivity within the dorsal FPN) varied according to the CPP build-up rate (Brosnan et al, 2020). In older adults, increasing evidence suggests that the SLF varies according to both levels of EE (Brosnan et al, 2021), and risk factors for neurocognitive decline (e.g. (Veldsman et al, 2020)).…”
Section: Discussionmentioning
confidence: 99%